Anode ablation and performance improvement of microcathode arc thruster. (8th March 2019) - Zolotukhin, D B; Hurley, S; Keidar, M
Abstract: This article presents the results of a study into the new concept of the microcathode arc thruster; a thruster with an ablative anode (AA- μ CAT). Such a thruster uses a triggerless discharge initiation, and has a coaxial electrode configuration where the central miniature anode is made of an ablative material (brass, solder, copper, etc), and an outer annular cathode, with optional magnetic coil. We show that the use of an ablative material (brass) increases the ion-to-arc current ratio from ∼2 to ∼4% without any focusing magnetic field, and up to 7% with a magnetic field of 0.33 T, compared with the case where the central anode is made of nonablative stainless steel, for the same pulsing power circuitry and parameters. For the first time, we demonstrate that even without a magnetic field, the AA- μ CAT has a higher thrust (7 μ N) and a higher thrust-to-power ratio (5.5 μ N W −1 ) with respect to the thruster with a nonablative refractory stainless steel anode (5.5 μ N and 4.8 μ N W −1, respectively). This fact is direct evidence of possible improvements to the microcathode arc thruster thrust-to-power ratio due to anode ablation.